Relationship between Job Stress and Coping Mechanism in Psychiatric Nurse in National Mental Health Hospital - Dwi Happy Anggia Sari; Mustikasari .; Ira Erwina (Faculty of Nursing, Universitas Andalas, 2018)
Background: Nursing has been considered one of the most stressfull professions. It also happens to nurses who work in the mental hospital. Coping mechanism known as a direct attempt to cope with the stress experienced. Purpose: To identify and explain the relationship between work stress coping mechanism in mental nurse. Method: using a cross sectional study design. Samples were examined as many as 92 people by means of sampling total sampling. Collecting data using instruments Psychiatric Nursing Occupational Stress Scale (PNOSS) and instruments The PsychNurse Methods of Coping Questionnaire (PNMCQ). For bivariate analysis using Independent T-test and for multivariate analysis using multiple linear regression test. Results: The results showed that nurses are female (81.5%), education level D3 (71.7%), married (65.2%), experienced moderate job stress (89.1%), the average age of 31 , 08 years, the average length of 52.95 months and work an average of 106.68 coping mechanisms. In the correlation analysis found a significant relationship between work stress coping mechanism in mental nurse (p = 0.000). Conclusion: The most dominant factor influencing stress coping mechanism is working. Recommended to the hospital to improve cooperation among nurses and other health care team, to clarify the duties of nurses and nursing care management stress to reduce job stress of nurses